2012
DOI: 10.1074/jbc.m111.268722
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing at C Terminus of CaV1.4 Calcium Channel Modulates Calcium-dependent Inactivation, Activation Potential, and Current Density

Abstract: Background: Alternative splicing diversifies calcium channel structure to change channel properties. Results: Extensive C-terminal alternative splicing generates channels differing in activation potential and voltage-and calciumdependent inactivation properties. Conclusion: Diversification of channel function through altered structure is fine-tuned by alternative splicing. Significance: Ca V 1.4 C-terminal splice variations recapitulate some aspects of native photoreceptor calcium currents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 48 publications
1
62
0
Order By: Relevance
“…Furthermore, it is predicted that mutations located at the C-terminus of the protein may not only influence the channel function, but also affect the binding of CABP4 to Cav1.4 C-terminus. Splice site mutation may affect the fine tuning of the channel as has been shown for alternative splicing of this channel in general (Tan et al, 2012). Mutations that do not show altered function in expression systems may involve sites needed for trafficking or for interaction with the ribbon synapse proteins.…”
Section: Molecules Important For Glutamate Releasementioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, it is predicted that mutations located at the C-terminus of the protein may not only influence the channel function, but also affect the binding of CABP4 to Cav1.4 C-terminus. Splice site mutation may affect the fine tuning of the channel as has been shown for alternative splicing of this channel in general (Tan et al, 2012). Mutations that do not show altered function in expression systems may involve sites needed for trafficking or for interaction with the ribbon synapse proteins.…”
Section: Molecules Important For Glutamate Releasementioning
confidence: 96%
“…In summary, mutations in CACNA1F, CABP4 and CACNA2D4 can be associated with loss or gain of function with insufficiently expressed genes resulting in altered or non-functional Cav1.4 channel activity, which is controlled by the auxiliary subunits (b, g and a2d) (Catterall et al, 2005), alternative splicing and associated regulatory proteins (Tan et al, 2012). Together, this disturbs the continuous release of glutamate from the photoreceptor synapse to the bipolar cells resulting in icCSNB, cone or cone-rod dystrophy phenotypes.…”
Section: Molecules Important For Glutamate Releasementioning
confidence: 98%
“…It has been shown that Cav1.4 splice variants lacking the ICDI domain exist under physiological conditions (38). In these channels, CDI is predicted to be switched off by the action of CaBP4.…”
Section: Cabp4 Regulates Cav14 Channelsmentioning
confidence: 99%
“…13 Splice variants of the Ca v 1.4 a 1 subunit lacking the CTD have been detected in human retina. 81 Therefore, while our present data indicate effects of CaBP4 dephosphorylation on Ca v 1.3 CDI, they are likely relevant for regulation of CDI of these Ca v 1.4 splice variants. It was previously reported that in retinal explants, OA increases Ca 2þ influx in a time-and dose-dependent manner, which is prevented by inhibitors of Ca v 1 Ca 2þ channels and PKC.…”
Section: Discussionmentioning
confidence: 68%